Facilitating Collaboration in Rare Genetic Disorders Through Effective Matchmaking in DECIPHER. Issue 10 (20th August 2015) - Chatzimichali, Eleni A.; Brent, Simon; Hutton, Benjamin; Perrett, Daniel; Wright, Caroline F.; Bevan, Andrew P.; Hurles, Matthew E.; Firth, Helen V.; Swaminathan, Ganesh J.
<x xml:space="preserve">Abstract</x> DECIPHER helps the clinical community share and compare human genome variants and phenotypes in a database of thousands of anonymous consented patients worldwide. Matchmaking using DECIPHER has resulted in the discovery of many new syndromes and led to over 700 peer‐reviewed publications.